PROPHETIC INTELLIGENCE DISCOURSE IN ISLAMIC RELIGIOUS EDUCATION - Suparman, Fatah; Subando, Joko; Abbas, Ngatmin (Proceeding of International Conference of Islamic Education, 2023)
This study aims to conduct a discourse on intelligence concepts IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient), and PI (Prophetic Intelligence) and the role of each intelligence in forming a perfect and noble human being. This study uses a qualitative approach with the method of literature study and theoretical analysis. This approach involves searching for and analyzing relevant theoretical sources to gain an in-depth understanding of the research topic. The method of literature study and theoretical analysis is used to describe the concepts that appear in the literature and build a solid conceptual framework. This approach is important in developing quality research and providing a holistic understanding of the topic under study. The results of this study indicate that in the discourse on intelligence, the concepts of IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient), and PI (Prophetic Intelligence) have differences and their respective roles. IQ is likened to "hardware" that affects a person's cognitive capacity, EQ as "software" that affects the quality of social relations, SQ as a moral core that directs values and goals for using intelligence, while PI (Prophetic Intelligence) focuses on understanding Uluhiyyah's monotheism and revelation taught by the Prophet Muhammad, in the form of awareness of death and preparation for facing it becomes an important element in PI. Within this whole intelligence discourse, this research demonstrates that the understanding and application of these concepts can have a positive impact on individuals, social relationships, and the meaningful and valued use of intelligence. Based on the research results, it was found that the importance of developing the concept of Prophetic Intelligence in Islamic religious education can help create good human beings or civilized human beings. The main goal of education is to produce humans who are fair to themselves and have the highest loyalty to the creator.